Discovery, Characterization, and Structure–Activity Relationships of an Inhibitor of Inward Rectifier Potassium (Kir) Channels with Preference for Kir2.3, Kir3.X, and Kir7.1 - Denton, Jerod S. (Frontiers in Pharmacology, 2011)
The inward rectifier family of potassium (Kir) channels is comprised of at least 16 family members exhibiting broad and often overlapping cellular, tissue or organ distributions. The discovery of disease-causing mutations in humans and experiments on knockout mice has underscored the importance of Kir channels in physiology and in some cases raised questions about their potential as drug targets. However, the paucity of potent and selective small-molecule modulators targeting specific family members has with few exceptions mired efforts to understand their physiology and assess their therapeutic potential. A growing body of evidence suggests that GIRK (G protein-regulated inward rectifier K) channels of the Kir3.X subfamily may represent novel targets for the treatment of atrial fibrillation. In an effort to expand the molecular pharmacology of GIRK, we performed a thallium (Tl+) flux-based high-throughput screen (HTS) of a Kir1.1 inhibitor library for modulators of GIRK. One compound, termed VU573, exhibited 10-fold selectivity for GIRK over Kir1.1 (IC50 = 1.9 M and 19 M, respectively) and was therefore selected for further study. In electrophysiological experiments performed on Xenopus laevis oocytes and mammalian cells, VU573 inhibited Kir3.1/3.2 (neuronal GIRK) and Kir3.1/3.4 (cardiac GIRK) channels with equal potency and preferentially inhibited GIRK, Kir2.3 and Kir7.1 over Kir1.1 and Kir2.1. Tl+ flux assays were established for Kir2.3 and the M125R pore mutant of Kir7.1 to support medicinal chemistry efforts to develop more potent and selective analogs for these channels. The structure-activity relationships of VU573 revealed few analogs with improved potency, however two compounds retained most of their activity toward GIRK and Kir2.3 and lost activity toward Kir7.1. We anticipate that the VU573 series will be useful for exploring the physiology and structure-function relationships of these Kir channels.